Elexacaftor/tezacaftor/ivacaftor and inflammation in children and adolescents with cystic fibrosis: a retrospective dual-center cohort study - Angela Pepe; Cristina Fevola; Daniela Dolce; Silvia Campana; Novella Ravenni; Giovanni Taccetti; Donatello Salvatore; Vito Terlizzi (Therapeutic Advances in Respiratory Disease)
Background: Cystic fibrosis (CF) is characterized by chronic neutrophilic inflammation in the airways. Elexacaftor/tezacaftor/ivacaftor (ETI) therapy has demonstrably improved clinical outcomes and quality of life in people with CF (pwCF), but its effects on systemic inflammatory parameters remain unclear. Objective: To evaluate the impact of ETI on systemic inflammation in children and adolescents with CF. Design: Retrospective, dual-center observational, propensity score-matching study of pediatric pwCF on ETI. Methods: PwCF aged ⩽ 18 years treated with ETI at two Italian reference centers were included in this study. Data on immunoglobulins (Ig) (A, G, and M), γ-globulin, leukocyte levels, percent predicted forced expiratory volume in the first second (ppFEV1), sweat chloride (SC) concentration, and sputum cultures were collected at baseline, 12, and 24 months of treatment. Laboratory data of a control group (pwCF, not in ETI therapy, same demographic characteristics as the study group) were also collected. Results: Sixty-six patients (30 males, median age: 12 years, F508del homozygous: 23) were included. Mean IgG levels (SD) significantly decreased ( p  = 0.001) from 1168.20 mg/dl (344.41) at baseline to 1093.05 mg/dl (258.73; 12 months) and 1092.87 mg/dl (232.42; 24 months). Similar reductions were observed for IgA and γ-globulin; IgM reduction was not statistically significant. Leukocyte levels also decreased significantly from 8.04 × 10 3 /µl (3.23 × 10 3 ) at baseline to 6.61 × 10 3 /µl (1.74 × 10 3 ) (12 months) and 6.45 × 10 3 /µl (1.70 × 10 3 ; 24 months). As for the control group, no significant changes in the levels of Ig, leukocytes, and γ-globulin were detected throughout the study period ( p  > 0.05). The mean (SD) ppFEV1 and the overall mean (SD) SC concentration significantly decreased during the follow-up. Regarding cultures, 18 (27%) of the 27 patients positive (41%) for Staphylococcus aureus at baseline became negative during treatment. Three patients (4%) with persistently positive cultures for Pseudomonas aeruginosa during the first 12 months, became negative after 24 months. One patient (1.5%), with a baseline positive culture for Pseudomonas Aeruginosa , showed negative cultures after 12 months. Conclusion: ETI treatment improved respiratory outcomes and significantly reduced values of IgG, IgA, γ-globulin, and leukocytes, suggesting an effect on the systemic inflammatory response. Further research is warranted to elucidate the role of inflammatory parameters in monitoring response to therapy.